INITIATING CITIZENS FIQH: SOLUTIONS FOR MINORITY MUSLIM IN NON-MUSLIM COUNTRIES - Ahmad Azaim Ibrahimy; Nawawi Nawawi; Wawan Juandi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
This article finds that fiqh has historical roots, where history has a functional relationship with ushul fiqh. what is referred to in terms of ushul fiqh with the causality of an event, namely asbāb al-nuzūl (chronological text of the verses of the Qur'an) and asbāb al-wurūd (chronological text of hadith). These two things have inspired the formation of civic fiqh that can be applied in non-Muslim countries. Because, Muslim minorities living in non-Muslim countries are very difficult to apply the teachings of Islam in a normal and comprehensive manner. Therefore, the application of civic fiqh has historical roots of the Prophet SAW and is in accordance with the historical process of its formation, namely: gradual, minimal burden, and no narrowness. The construction of civic fiqh for the Muslim minority is an emergency. That is, if one day the conditions are good and normal, then Islam must be carried out comprehensively. Islam has two eternal dimensions that always survive (tsawabit) and are flexible according to benefit (taghayyurat).